Method for manufacturing flexible metal airgel using heterogeneous nanomaterials

KR103032369B1Active Publication Date: 2026-10-13CHUNG ANG UNIV IND ACADEMIC COOP FOUND
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020240006851
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2026-10-13
Estimated Expiration
2044-01-16

Smart Images

  • Figure 112024005945924-PAT00001_ABST
    Figure 112024005945924-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials, and more specifically, to a method for manufacturing a metal aerogel comprising the steps of: preparing suspensions of different one-dimensional nanomaterials; freezing the suspensions on a substrate; and sublimating them.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials. More specifically, it relates to a metal aerogel that is very flexible, has high strength, and has excellent conductivity, manufactured by assembling an ice template of cellulose nanofibers (CNF) with strong hydrogen bonds and silver nanowires. Background Technology

[0002] Aerogel is a superporous material having nanopores of about 20 to 50 nm with a porosity of over 95%. It is produced by reacting raw materials in a sol-gel manner to create a nanostructured gel containing a large amount of solvent, and then removing the solvent with almost no shrinkage using a method such as supercritical drying, so that the original nanostructure of the gel is maintained.

[0003] The extremely low thermal conductivity of aerogels is attributed to their high porosity and the effect of their unique nanoporous structure in blocking the movement of air molecules that can occur in gases.

[0004] Generally speaking, these aerogels are a type of porous silicone particle and have excellent thermal insulation effects due to their high porosity. However, very small particles often scatter and fly around in the workspace and escape from the insulation material, weakening the thermal insulation function. Therefore, there were many difficulties in making fabrics with this material and in manufacturing and processing products using this fabric.

[0005] US Public Patent US20070208124 introduces a technology for manufacturing nanoclay aerogel polymer composite materials and states that the final product is made by using various types of nanoclays and various block copolymers, undergoing a “sol-gel” process, and that more than 90% of the moisture present is removed by freeze-drying.

[0006] US Published Patent US2013 / 0018112 proposes a technology for manufacturing nanocellulose composite aerogels, hydroaerogels, organic aerogels, etc. by using cellulose nanocrystals at a concentration of 50-80% w / w and including multi-walled carbon nanotubes, gold nanoparticles, silver nanoparticles, platinum nanoparticles, etc.

[0007] Conventional manufacturing processes for metal aerogels generally utilize the sol-gel process and self-propagating high-temperature synthesis.

[0008] Although this process is simple and fast, the problem remains that the manufactured aerogel has low strength and is inherently brittle.

[0009] Meanwhile, ice templates are an efficient method for manufacturing aerogel.

[0010] Through this process, a variety of materials constituting the aerogel can be selected to form a desirable 3D porous structure.

[0011] However, these conventional applications generally focused on thermal insulation, self-cleaning surfaces, and EMI shielding that do not require mechanical deformation. Prior art literature

[0012] US Published Patent US2013 / 0018112 Republic of Korea Registered Patent 10-1691198 Republic of Korea Registered Patent 10-2194580 Japan Registered Patent JP 7223523 Republic of Korea Published Patent 10-2015-0086570 The problem to be solved

[0013] Accordingly, the present invention has been devised to solve the aforementioned conventional problems, and according to an embodiment of the present invention, the purpose is to provide a method for manufacturing a flexible and strong metal aerogel through an ice template process applicable to a multifunctional sensor.

[0014] And according to an embodiment of the present invention, the purpose is to provide a highly flexible, strong, and highly conductive aerogel manufactured by assembling an ice template of CNF and AgNWs having strong hydrogen bonds.

[0015] According to an embodiment of the present invention, the aerogel is composed of heterogeneous 1D nanomaterials such as cellulose nanofibers (CNF) and silver nanowires (AgNW) aligned parallel to the growth direction of ice crystals, and additionally, by adding 0.5 wt% of polyvinyl alcohol (PVA) to form hydrogen bonds, the adhesion between CNF and AgNW is strengthened, thereby significantly improving the compressive modulus to 71.3% and the yield strength to 74.5%. The purpose is to provide a method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials.

[0016] According to an embodiment of the present invention, the purpose is to provide an aerogel having characteristics such as an anisotropic structure, low density (~17.55 mg / ml), low resistivity (~0.005 Ω·m), high elastic modulus (~34.9 kPa), and high yield strength (~3.9 kPa).

[0017] According to an embodiment of the present invention, the purpose is to provide a method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials, which demonstrates successful application as a piezoresistive force sensor and a thermal pressure sensor, and not only overcomes the fragility of existing aerogels but also expands the range of applications as a multifunctional physical sensor.

[0018] Meanwhile, the technical problems to be solved by the present invention are not limited to those mentioned above, and other technical problems not mentioned will be clearly understood by those skilled in the art to which the present invention belongs from the description below. means of solving the problem

[0019] The first objective of the present invention can be achieved by a method for manufacturing a metal aerogel, characterized by comprising the steps of: preparing suspensions of different one-dimensional nanomaterials; freezing the suspensions on a substrate; and sublimating them.

[0020] And the above-mentioned one-dimensional nanomaterial suspension may be characterized by including nanowires and nanofibers.

[0021] In addition, the above nanowires may be characterized as silver nanowires (AgNW) and the above nanofibers as cellulose nanofibers (CNF).

[0022] And in the step of preparing the above suspension, polyvinyl alcohol may be added to the silver nanowires and the cellulose nanofibers.

[0023] In addition, the above polyvinyl alcohol may be characterized as being 0.4 to 0.6 weight%.

[0024] And the above silver nanowires may be characterized by being 67 weight% or more.

[0025] In addition, the step of freezing the suspension on the substrate may be characterized by placing the suspension into a mold on a low-temperature copper plate and freezing it.

[0026] And the above low temperature can be characterized as being -70 to -50℃.

[0027] In addition, in the freezing step described above, the ice crystals form nuclei and grow according to the temperature gradient, and at the same time, the nanomaterial is excluded from the grown ice crystals to form a fiber structure.

[0028] And in the above sublimation step, the ice crystals are removed through sublimation, and the combined silver nanowires and cellulose nanofibers are formed in a flexible, low-density porous structure.

[0029] In addition, the above sublimation step may be characterized by proceeding for 45 to 50 hours.

[0030] The second objective of the present invention can be achieved as a flexible metal aerogel using heterogeneous nanomaterials, characterized by being manufactured by the manufacturing method according to the first objective mentioned above.

[0031] The third objective of the present invention can be achieved as a sensor characterized by comprising a flexible metal aerogel using heterogeneous nanomaterials according to the second objective mentioned above.

[0032] The fourth objective of the present invention can be achieved as a piezoresistive force sensor characterized by comprising a flexible metal aerogel using heterogeneous nanomaterials according to the second objective mentioned above.

[0033] The fifth objective of the present invention can be achieved as a thermal pressure sensor characterized by comprising a flexible metal aerogel using heterogeneous nanomaterials according to the second objective mentioned above. Effects of the invention

[0034] According to an embodiment of the present invention, a method for manufacturing a flexible and strong metal aerogel through an ice template process applicable to a multifunctional sensor can be provided.

[0035] And according to an embodiment of the present invention, a highly flexible, strong, and highly conductive aerogel can be provided by assembling an ice template of CNF and AgNWs having strong hydrogen bonds.

[0036] According to the method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials according to an embodiment of the present invention, the aerogel is composed of heterogeneous 1D nanomaterials such as cellulose nanofibers (CNF) and silver nanowires (AgNW) aligned parallel to the growth direction of ice crystals, and additionally, by adding 0.5 wt% of polyvinyl alcohol (PVA) to form hydrogen bonds, the adhesion between CNF and AgNW is strengthened, thereby having the effect of significantly improving the compressive modulus to 71.3% and the yield strength to 74.5%.

[0037] According to the method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials according to an embodiment of the present invention, it has the effect of having characteristics such as an anisotropic structure, low density (~17.55 mg / ml), low resistivity (~0.005 Ω·m), high elastic modulus (~34.9 kPa), and high yield strength (~3.9 kPa).

[0038] According to an embodiment of the present invention, successful application as a piezoresistive force sensor and a thermal pressure sensor has been demonstrated. Furthermore, according to the method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials according to an embodiment of the present invention, it has the advantage of not only overcoming the fragility of existing aerogels but also expanding the range of applications as a multifunctional physical sensor.

[0039] Meanwhile, the effects obtainable from the present invention are not limited to those mentioned above, and other unmentioned effects will be clearly understood by those skilled in the art to which the present invention belongs from the description below. Brief explanation of the drawing

[0040] The following drawings attached to this specification illustrate preferred embodiments of the present invention and serve to further enhance understanding of the technical concept of the present invention together with the detailed description of the invention; therefore, the present invention should not be interpreted as being limited only to the matters described in such drawings. FIG. 1 is a schematic diagram of the preparation of an ice template of an AgNW / CNF / PVA-based aerogel according to an embodiment of the present invention. FIG. 2 shows (a) a photograph of an aerogel showing flexibility and lightness according to an experimental example of the present invention, (b,c) SEM images of the aerogel (the top view of (b) shows the porous structure, and the side view of (c) shows the nanomaterial assembled according to the temperature gradient applied during the manufacturing process), FIG. 3 shows the formation of hydrogen bonds and the homogeneous distribution of nanomaterials by (a) FT-IR and (b) EDS elemental mapping of the aerogel according to an experimental example of the present invention. FIG. 4 shows the compressive mechanical properties of an aerogel according to an experimental example of the present invention, including (a,b) stress-strain curves of an aerogel having varying amounts of AgNW (a) and PVA (b), (c) compression modulus and yield strength according to the composition of the aerogel, and (d) cyclic compressive stress-strain curve of SNA-80PVA. FIG. 5 shows, according to an experimental example of the present invention, (a) linear IV curves of aerogels with various compositions and (b) electrical resistivity, (c) change in reversible resistance when bent up to 2.58 mm, and (d) highly sensitive compression pressure detected at less than 1.3 kPa for 12 cycles. Figure 6 illustrates, according to an experimental example of the present invention, (a) the TCR of the aerogel, (b,c) the transient response of the aerogel to continuously changing vacuum pressure, and (d) a change in relative resistance that is highly linear and sensitive to changes in vacuum pressure. Specific details for implementing the invention

[0041] The above objects, other objects, features, and advantages of the present invention will be easily understood through the following preferred embodiments associated with the accompanying drawings. However, the present invention is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete and to ensure that the spirit of the invention is sufficiently conveyed to a person skilled in the art.

[0042] In this specification, when a component is described as being on another component, it means that it may be formed directly on the other component or that a third component may be interposed between them. Also, in the drawings, the thicknesses of the components are exaggerated for the effective description of the technical content.

[0043] The embodiments described herein will be explained with reference to cross-sectional and / or plan views, which are exemplary illustrations of the invention. In the drawings, the thicknesses of films and regions are exaggerated for effective explanation of the technical content. Accordingly, the shapes of the exemplary drawings may be modified by manufacturing techniques and / or tolerances, etc. Accordingly, the embodiments of the invention are not limited to the specific shapes depicted but include variations in shape produced according to the manufacturing process. For example, a region depicted as a right angle may be rounded or have a certain curvature. Accordingly, the regions illustrated in the drawings have properties, and the shapes of the regions illustrated in the drawings are intended to illustrate specific shapes of the regions of the device and are not intended to limit the scope of the invention. Although terms such as first, second, etc., have been used to describe various components in the various embodiments of this specification, these components should not be limited by such terms. These terms are used merely to distinguish one component from another. The embodiments described and illustrated herein also include their complementary embodiments.

[0044] The terms used herein are for describing the embodiments and are not intended to limit the invention. In this specification, the singular form includes the plural form unless specifically stated otherwise in the text. As used herein, 'comprises' and / or 'comprising' do not exclude the presence or addition of one or more other components to the mentioned components.

[0045] In describing the specific embodiments below, various specific details have been included to explain the invention more specifically and to aid understanding. However, a reader with sufficient knowledge in the art to understand the invention will recognize that it can be used without these various specific details. In some cases, it is noted in advance that commonly known aspects that are not significantly related to the invention have been omitted to prevent unnecessary confusion in describing the invention.

[0047] Hereinafter, a method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials according to an embodiment of the present invention will be described.

[0048] Figure 1 illustrates a schematic diagram of the preparation of an ice template of an AgNW / CNF / PVA-based aerogel according to an embodiment of the present invention.

[0049] According to an embodiment of the present invention, a method for manufacturing a flexible and strong metal aerogel through an ice template process applicable to a multifunctional sensor can be provided.

[0050] And according to an embodiment of the present invention, a highly flexible, strong, and highly conductive aerogel can be provided by assembling an ice template of CNF and AgNWs having strong hydrogen bonds.

[0051] A method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials according to an embodiment of the present invention first prepares suspensions of different one-dimensional nanomaterials.

[0052] Suspensions mixed with such one-dimensional nanomaterials may include nanowires and nanofibers.

[0053] And in an embodiment of the present invention, the nanowire may be composed of silver nanowires (AgNW), and the nanofiber may be composed of cellulose nanofibers (CNF).

[0054] In addition, in the step of preparing such a suspension, polyvinyl alcohol can be added to the silver nanowires and the cellulose nanofibers to form hydrogen bonds between the silver nanowires and the cellulose nanofibers, thereby strengthening the adhesive strength. In an embodiment of the present invention, it is preferable that such polyvinyl alcohol (PVA) be added in an amount of 0.4 to 0.6 weight%.

[0055] In addition, the silver nanowires make up more than 67 weight percent.

[0056] Then, this suspension is frozen on a substrate. In an embodiment of the present invention, the suspension is placed into a mold on a low-temperature copper plate and frozen. In an embodiment of the present invention, the low-temperature copper plate is approximately -70 to -50°C.

[0057] And during this freezing step, ice crystals nucleate and grow according to the temperature gradient, and at the same time, nanomaterials are excluded from the grown ice crystals to form a fiber structure.

[0058] Then, sublimation is carried out for about 45 to 50 hours. During this sublimation step, ice crystals are removed through sublimation, and the combined silver nanowires and cellulose nanofibers are formed into a flexible, low-density porous structure.

[0060] Below, experimental results regarding the aerogel prepared according to the previously mentioned embodiment of the present invention will be described.

[0061] FIG. 2 shows (a) a photograph of an aerogel showing flexibility and lightness, and (b,c) SEM images of the aerogel according to an experimental example of the present invention. The top view of FIG. 2(b) shows a porous structure, and the side view of FIG. 2(c) shows a nanomaterial assembled according to a temperature gradient applied during the manufacturing process.

[0062] As illustrated in Figure 1 mentioned above, the metal aerosol applied in the experimental example of the present invention was an AgNWs / CNFs / PVA suspension that was frozen on a low-temperature copper plate (<-60°C) inside a PTFE mold and then sublimated for 48 hours. During the freezing process, ice crystals nucleate and grow according to the temperature gradient, and at the same time, nanomaterials are excluded from the grown ice crystals to form a fiber-like structure.

[0063] Then, freeze-drying removes ice crystals through sublimation, leaving the assembled AgNW / CNF in the form of a flexible, low-density porous structure as shown in the optical and scanning electron microscope (SEM) images of Fig. 2.

[0064] Figure 3 shows the formation of hydrogen bonds and the homogeneous distribution of nanomaterials by (a) FT-IR and (b) EDS elemental mapping of the aerogel according to an experimental example of the present invention.

[0065] As shown in Fig. 3, Fourier transform infrared spectroscopy (FT-IR) shows the formation of hydrogen bonds between nanomaterials, and energy dispersive spectroscopy (EDS) elemental mapping shows homogeneously assembled AgNW / CNF.

[0066] Aerogel is denoted as SNA-x, where x represents the weight ratio of AgNWs.

[0067] FIG. 4 illustrates the compressive mechanical properties of an aerogel according to an experimental example of the present invention, including (a,b) stress-strain curves of an aerogel having varying amounts of AgNW (a) and PVA (b), (c) compression modulus and yield strength according to the composition of the aerogel, and (d) cyclic compressive stress-strain curve of SNA-80PVA.

[0068] That is, Figures 4a and 4b show the compressive stress-strain curves of aerogels with different weight ratios of AgNWs and PVA. It can be seen that the compressive strength increases as the amount of AgNWs increases.

[0069] In particular, as shown in Fig. 4c, adding 0.5 wt% of PVA significantly improves the elastic modulus and yield strength by 71.3% and 74.5%, respectively, and as shown in Fig. 4d, it can be seen that the aerogel (SNA-80) can have elasticity and can be compressed up to a maximum deformation of 5%.

[0070] FIG. 5 shows (a) linear IV curves of aerogels with various compositions and (b) electrical resistivity, (c) change in reversible resistance when bent up to 2.58 mm, and (d) very sensitive compressive pressure detected at less than 1.3 kPa for 12 cycles, according to an experimental example of the present invention.

[0071] As shown in Figures 5a and 5b, it can be seen that AgNWs improve the conductivity of the aerogel, particularly at 67 wt% or more.

[0072] And as shown in Fig. 5c, it can be seen that all these characteristics enable the electromechanical characterization of flexible aerogel, including reversible bending up to 2.58 mm.

[0073] In addition, the aerogel demonstrates a highly sensitive and stable response of ~3800% under pressure of 1.3 kPa, proving its potential for application as a piezoresistive force sensor.

[0074] Figure 6 illustrates, according to an experimental example of the present invention, (a) the TCR of the aerogel, (b,c) the transient response of the aerogel to continuously changing vacuum pressure, and (d) a change in relative resistance that is highly linear and sensitive to changes in vacuum pressure.

[0075] As shown in Figs. 6a and 6b, heat transfer vacuum pressure sensing was experimented upon based on the measured temperature resistance coefficient (TCR) of an aerogel (0.22% / °C). As shown in Figs. 6c and 6d, it can be seen that high porosity allows heat to be efficiently transferred from the aerogel to surrounding molecules, thereby enabling rapid monitoring of small pressure changes with high sensitivity (0.4% / Pa).

[0077] As mentioned above, according to the method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials according to an embodiment of the present invention, a highly flexible, strong, and highly conductive aerogel can be provided by assembling an ice template of CNF and AgNW having strong hydrogen bonds.

[0078] According to the method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials according to an embodiment of the present invention, the aerogel is composed of heterogeneous 1D nanomaterials such as cellulose nanofibers (CNF) and silver nanowires (AgNW) aligned parallel to the growth direction of ice crystals, and additionally, by adding 0.5 wt% of polyvinyl alcohol (PVA) to form hydrogen bonds and strengthen the adhesion between CNF and AgNW, the compressive modulus can be significantly improved to 71.3% and the yield strength to 74.5%.

[0079] According to the method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials according to an embodiment of the present invention, the material may have characteristics such as an anisotropic structure, low density (~17.55 mg / ml), low resistivity (~0.005 Ω·m), high elastic modulus (~34.9 kPa), and high yield strength (~3.9 kPa).

[0080] According to the experimental examples of the present invention, successful applications as piezoresistive force sensors and thermal pressure sensors have been demonstrated, and according to the method for manufacturing flexible metal aerogels using heterogeneous nanomaterials according to the embodiments of the present invention, not only can the fragility of existing aerogels be overcome, but the range of applications can also be expanded to include multifunctional physical sensors.

[0082] In addition, the apparatus and method described above are not limited to the configurations and methods of the embodiments described above; rather, all or part of each embodiment may be selectively combined to allow for various modifications to be made.

Claims

Claim 1 A method for manufacturing a metal aerogel comprises the steps of: preparing suspensions of different one-dimensional nanomaterials; and freezing the suspensions on a substrate. The method comprises the step of sublimating; wherein the one-dimensional nanomaterial suspension comprises nanowires and nanofibers, wherein the nanowires are silver nanowires (AgNW) and the nanofibers are cellulose nanofibers (CNF), wherein polyvinyl alcohol is added to the silver nanowires and cellulose nanofibers in the step of preparing the suspension, wherein the polyvinyl alcohol is 0.45 to 0.55 wt%, wherein the silver nanowires in the aerogel are 67 to 80 wt%, and wherein the aerogel has a piezoresistive reaction in which the rate of change of current reaches 3800% under a pressure of 1.3 kPa, and wherein the step of freezing the suspension on the substrate comprises placing the suspension into a mold on a copper plate and freezing it at -70 to -50°C, wherein in the freezing step, ice crystals form nuclei and grow according to the temperature gradient, and simultaneously, the nanomaterial is excluded from the grown ice crystals to form a fiber structure A method for manufacturing a flexible metal aerogel using heterogeneous nanomaterials, characterized in that, in the sublimation step, ice crystals are removed through sublimation and the combined silver nanowires and cellulose nanofibers are formed in a flexible and porous structural form, the sublimation step is carried out for 45 to 50 hours, the aerogel is composed of heterogeneous 1D nanomaterials, namely cellulose nanofibers (CNF) and silver nanowires (AgNW), aligned parallel to the growth direction of the ice crystals, hydrogen bonds are formed by adding 0.45 to 0.55 wt% of polyvinyl alcohol (PVA) to strengthen the adhesion between CNF and AgNW, and the aerogel is applied as a piezoresistive force sensor and a heat transfer pressure sensor. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 delete Claim 11 delete Claim 12 A flexible metal aerogel using heterogeneous nanomaterials, characterized as a metal aerogel manufactured by the manufacturing method according to claim 1. Claim 13 A sensor characterized by comprising, as a sensor, a flexible metal aerogel using a heterogeneous nanomaterial according to claim 12. Claim 14 A piezoresistive force sensor characterized by comprising, as a force sensor, a flexible metal aerogel using a heterogeneous nanomaterial according to claim 12. Claim 15 A thermal pressure sensor characterized by comprising, as a pressure sensor, a flexible metal aerogel using a heterogeneous nanomaterial according to claim 12.

Citation Information

Patent Citations

  • Aerogel powder and manufacturing method of the same

    KR1020200001167A

  • Nanofiber-nanowire composite and fabrication method thereof

    US20110177332A1

  • Shape Memory Alloy Actuators And Methods Thereof

    US20210131405A1